19-year remotely sensed data in the forecast of spectral models of the environment. Issue 8 (3rd August 2021) - Rossi, Fernando Saragosa; Silva Junior, Carlos Antonio da; Oliveira-Júnior, José Francisco de; Teodoro, Paulo Eduardo; Shiratsuchi, Luciano Shozo; Lima, Mendelson; Teodoro, Larissa Pereira Ribeiro; Tiago, Auana Vicente; Capristo-Silva, Guilherme Fernando
ABSTRACT: The aims of this study were: i) to compare no-till areas in two municipalities located in different regions of Brazil, along with the influence on CO2 Flux and GPP, and ii) to verify the difference between environmental factors followed by the trends of these variables regarding future scenarios (ARIMA time-series model number). The study was carried out in two areas with different latitudes in the municipalities of Sinop-MT and Passo Fundo-RS, both in Brazil. A time series of 19 years was performed with data acquired by remote sensing from the following satellites: i) Landsat-8 (OLI and TIRS), and ii) TERRA/AQUA (MODIS). The results propound that the spectro-temporal variables are directly influenced by soil management and agricultural practices over the observation time, with a satisfactory correlation in future predictions of the variables for the next ten years, in which presented that the variation of GPP and albedo values for the two study sites would gradually increase until 2028 and the temperature remained constant between the range of its seasonality, and CO2 Flux tends to decrease in its seasonality, indicating a higher CO2 absorption.